Mitochondrial Oxygenation During Cardiopulmonary Bypass: A Pilot Study - Harms, Floor A.; Ubbink, Rinse; de Wijs, Calvin J.; Ligtenberg, Max P.; ter Horst, Maarten; Mik, Egbert G. (Frontiers in Medicine, 2022)
Objective Ensuring adequate oxygenation is essential for the preservation of organ function during cardiac-surgery and cardiopulmonary bypass (CPB). Both hypoxia and hyperoxia result in undesired outcomes and a narrow window for optimal oxygenation exists. Current perioperative monitoring techniques are not always sufficient to monitor adequate oxygenation. The non-invasive COMET® could be a new monitoring tool, measuring mitochondrial oxygen tension (mitoPO2). This pilot study examines the feasibility of cutaneous mitoPO2 measurements during cardiothoracic procedures. The cutaneous mitoPO2 will be compared to tissue oxygenation (StO2) as measured by Near Infrared Spectroscopy. Design and method This single center observational study examined 41 cardiac-surgery patients requiring CPB. Pre-operatively, patients received a 5-aminolevulinc acid plaster on the upper arm to enable the mitoPO2 measurements. After induction of anesthesia, both the cutaneous mitoPO2 and StO2 were measured throughout the procedure. Patients were observed until discharge for the development of acute kidney insufficiency (AKI). 1.3 Results The cutaneous mitoPO2 was successfully measured in all patients and was 63.5 [40.0 – 74.8] mmHg at the surgery start and decreased significantly (p<0.01) to 36.4 [18.4 – 56.0] mmHg by the end of the CPB run. The StO2 at surgery start was 80.5 [76.8-84.3] %, and did not change significantly. Cross-clamping of the aorta and the switch to non-pulsatile flow resulted in a median cutaneous mitoPO¬2 decrease of 7 mmHg (p<0.01). The cessation of the aortic cross-clamping period resulted in an increase of 4 mmHg (p<0.01). Four patients developed AKI these all had a lower pre-operative eGFR of 52 ml/min versus 81 ml/min in the non-AKI group. The AKI group spent 32% of the operation time with a cutaneous mitoPO2¬ value under 20 mmHg as compared to 8% in the non-AKI group. Conclusion This pilot study illustrated the feasibility of measuring the cutaneous mitoPO2 with the COMET® during cardiothoracic procedures. Moreover, in contrast to StO2, the mitoPO2 decreased significantly with increased CPB run time. The cutaneous mitoPO2 also significantly decreased during the aortic cross-clamping period and increased upon release of the clamp, the StO2 did not. This emphasized the sensitivity of the cutaneous mitoPO2 to detect circulatory and microvascular changes.